2023
DOI: 10.3390/microorganisms11010140
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety and Probiotic Characteristics of Lacticaseibacillus rhamnosus X253 via Complete Genome and Phenotype Analysis

Abstract: Lacticaseibacillus rhamnosus is a generalist that can adapt to different ecological niches, serving as a valuable source of probiotics. The genome of L. rhamnosus X253 contains one chromosome and no plasmids, with a size of 2.99 Mb. Both single-copy orthologous gene-based phylogenetic analysis and average nucleotide identity indicated that dairy-derived L. rhamnosus X253 was most closely related to the human-intestine-derived strain L. rhamnosus LOCK908, rather than other dairy strains. The adaptation of L. rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Therefore, it is necessary to study the distribution of antibiotic-resistance genes in probiotics and the antibiotic resistance pattern of strains [ 61 ]. Similar to commercial probiotic strain LGG, the same resistance gene was identified for L. plantarum LPJZ-658 in the CARD database with coverage >40% and identity >75% [ 48 ]. Furthermore, the antibiotic susceptibility of L. plantarum LPJZ-658 was further investigated, and the results indicated that L. plantarum LPJZ-658 was sensitive or intermediate sensitive to seven antibiotics, including ampicillin, erythromycin, gentamicin, midecamycin, streptomycin, chloramphenicol, and clindamycin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to study the distribution of antibiotic-resistance genes in probiotics and the antibiotic resistance pattern of strains [ 61 ]. Similar to commercial probiotic strain LGG, the same resistance gene was identified for L. plantarum LPJZ-658 in the CARD database with coverage >40% and identity >75% [ 48 ]. Furthermore, the antibiotic susceptibility of L. plantarum LPJZ-658 was further investigated, and the results indicated that L. plantarum LPJZ-658 was sensitive or intermediate sensitive to seven antibiotics, including ampicillin, erythromycin, gentamicin, midecamycin, streptomycin, chloramphenicol, and clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…The behavior, death, and poisoning of the mice were observed, and the average weight per mouse was calculated once a day. The acid and bile salt tolerance of L. plantarum LPJZ-658 was detected as previously described with some modification [48]. For acid tolerance of L. plantarum LPJZ-658, the active grown cells were harvested, washed with phosphate-buffered saline (PBS) buffer, and resuspended in an equal volume of MRS broth with pH adjusted to 3.0, and then 100 µL aliquots were obtained at different time intervals (0 h and 3 h) for gradient dilution.…”
Section: Oral Toxicity Analysis Of L Plantarum Lpjz-658mentioning
confidence: 99%
“…Only the strains exhibiting gamma haemolysis were considered safe. The selected LAB isolates were then subjected to antibiotic assays, with Staphylococcus aureus serving as a positive control, showing a visible clear zone for beta haemolysis [32].…”
Section: Haemolytic Activitymentioning
confidence: 99%
“…Genetic manipulation is an important tool to study probiotic mechanisms of action e.g., by using isogenic mutant strains, and to potentially create improved strains. However, a scarcity of enough genetic tools out there for a few probiotic species, particularly food-grade systems for Bifidobacteria, and a legal framework for the utilization of genetically manipulated/enhanced organisms limits the analysis progress above 45 . However, It is not common to send genetic constructs to biological repositories.…”
Section: Considerations For Research In Probioticsmentioning
confidence: 99%